Metal/oxide Composites: Mechanisms of the Formation from the Thermal Decomposition of LaNi5 - Torresan, Maria Fernanda (2015)
The formation of metal/oxide composites from the thermal decomposition of LaNi5 is analyzed by TG and DSC between room temperature and 700 °C. The reaction products are characterized by XRD, SEM and EDS. Based on the results obtained, the following global mechanisms are proposed: For temperature range between 160 °C and 600 °C 2LaNi5 + 13/2O2→La2O3 + 10NiO(1) For temperature range higher than 600 °C, two mechanisms were proposed as presented for each following equation: LaNi5 + 7/2O2→ LaNiO3 + 4NiO (2) 2LaNi5 + 7/2O2→ La2O3 + Ni → La2O3 + NiO → LaNiO3 + 10NiO (3) The conditions that promote the formation of metal/oxide composites are discussed according to these results..